Development of Mathematics e-Modules based on PjBL STEM on Materials Constructing Flat Side Spaces to Improve Mathematical Communication Ability of Junior High School Students - Seftiana Wandani; Reza Kusuma Setyansah; Titin Masfingatin (AL-ISHLAH: Jurnal Pendidikan, 2023)
This development research aims: 1) To find out the validity, practicality, and effectiveness of the PjBL STEM-based Mathematics e-Module on the material of Constructing Flat Side Spaces. 2) Knowing the increase in mathematical communication skills of class VIII B students of SMPN 2 Sawahan after using the PjBL STEM-based Mathematics e-Module. The development model in this research uses 4D which consists of Define, Design, Development, and Dissemination. The instruments used include a learning device validation sheet to determine the validity of the developed e-module, student response questionnaires to determine the practicality of the developed e-module, and learning outcomes tests to determine the effectiveness of the developed e-module. The results showed: 1) the PjBL STEM-based Mathematics e-Module on the Flat Sided Space Building material met the validity criteria, the average validation sheet obtained a value of 94% with the "very valid" category, and the practicality criteria obtained from the student response questionnaire sheet reached a score of 62 % in the field trial with the practical category, and the effectiveness criteria tested using the t-test met the specified criteria, the post-test value of the experimental class was 4.75 greater than the control class and the p-value = 0.015 0.05 means that there is a difference in scores student learning outcomes significantly in the experimental class and control class. 2) The improvement of students' mathematical communication skills can be seen after using the developed e-Module. This can be seen from the results of the normalized gain test with an average N-Gain score of 0.63 (medium level of interpretation). So that it proves that the development of e-Modules developed can improve students' communication skills. Based on the results of the study, it is concluded that the PjBL STEM-based Mathematics e-Module developed by researchers can improve students' mathematical communication skills and is suitable for use in learning